Refleksi Kepemimpinan Perempuan pada Kelompok Wanita Tani Wanayasa - Sabila, Muthia Fithri; Yuliani, Nadya Amalia; Hazar, Dilpa Alifia; Iqva, Valdio (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2023)
Abstract. Leadership by women has an important role in the development of society today. A number of studies have shown that the representation of women at the management level. Based on research by the World Economic Forum, Indonesia itself is still ranked 101 out of 156 countries for gender equality. The purpose of this research is to find out about the leadership style of women in KWT Wanayasa. In this study using a qualitative descriptive method by observing interviews directly with the chairperson, secretary and members of the Women Farmers Group. The object of this research is the leadership of the Women Farmers Group and the subject of this research is the Chairperson of KWT Wanayasa. This study uses source, time and technique triangulation. where uses various techniques, namely observation, interviews, and documentation. The results of this research show that the leadership style most often applied by the chairman of KWT Wanayasa is a democratic leadership style with the characteristics of the mother leader in carrying out their functions as an active farmer group, this is influenced by the presence of one figure to increase the performance of members and create a good teamwork relationship.